(3GdHTGQI hGdfPGQI aj JYHjQ GdQDjGs - (3YHO Gdedc Hf eMeO Hf EHQGgje GdfjSGHhQj GdNQchTj, CHh SYO,J (B407 (3g` s ((3CMeO GdaGJM GdMdHi s)
(3ChdgG (B:s
(3hHYO aEfg deG cGfJ GdQDjG GdUMjMI ai GdCUd eHjfI Ydi MbGFb GdCMhGd hGdCehQ s
(3BNQgG (B:s
(3QCjJ GSe Gddg GdCYXe ai Gdfhe ai Qb(B: (3Gddg GdQMef GdQMje GdUeO fLR GdcJGH HYhf Gddg hMSf Jhajbg s
(3HQSe NRGfI CjHc GdOhGOGQ GdSjais
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B188s
Keywords: (3JYHjQ GdQDjGs